The determinants of customer knowledge sharing behavior: A review study - Sari H.; Othman M.; Al-Ghaili A.M. (Springer Verlag, 2023)
Competition; Knowledge acquisition; Sales; Soft computing; Competitive advantage; Customer knowledge; Customer knowledge management; Enjoyment of helpings; Knowledge-sharing; Perceived ease of use; Psychological factors; Technological factors; Knowledge management